Metadiscursive Strategies in Self-help Books - Díaz Blanca, Lourdes Ángela (2023)
An analysis is provided of the metadiscursive strategies used in self-help books to handle the commitment with their readers and reach the communicative purposes of the genre. The inquiry is based on the metadiscursive model. It follows a descriptive and exploratory design with an inductive-deductive character. It was found that the prevailing strategy to commit with the readers is the reference made to the reader, followed by directive strategies, and the appeal to shared knowledge. Ties with the reader are established by using questions and personal comments.